The Search Engine for Multi‐Proteoform Complexes: An Online Tool for the Identification and Stoichiometry Determination of Protein Complexes. Issue 1 (8th December 2016) - Skinner, Owen S.; Schachner, Luis F.; Kelleher, Neil L.
Abstract: Recent advances in top‐down mass spectrometry using native electrospray now enable the analysis of intact protein complexes with relatively small sample amounts in an untargeted mode. Here, we describe how to characterize both homo‐ and heteropolymeric complexes with high molecular specificity using input data produced by tandem mass spectrometry of whole protein assemblies. The tool described is a "search engine for multi‐proteoform complexes, " (SEMPC) and is available for free online. The output is a list of candidate multi‐proteoform complexes and scoring metrics, which are used to define a distinct set of one or more unique protein subunits, their overall stoichiometry in the intact complex, and their pre‐ and post‐translational modifications. Thus, we present an approach for the identification and characterization of intact protein complexes from native mass spectrometry data. © 2016 by John Wiley & Sons, Inc.